Adaptation to Climate Change: A Spatial Challenge - Roggema, Rob (Springer Netherlands : Imprint: Springer, 2009)
As it becomes clear that climate change is not easily within the boundaries of the 1990's, society needs to be prepared and needs to anticipate future changes due to the uncertain changes in climate. So far, extensive research has been carried out on several issues including the coastal defence or shifting ecozones. However, the role spatial design and planning can play in adapting to climate change has not yet been focussed on. This book illuminates the way adaptation to climate change is tackled in water management, ecology, coastal defence, the urban environment and energy. The question posed is how each sector can anticipate climate change by creating spatial designs and plans. The main message of this book is that spatial design and planning are a very useful tool in adapting to climate change. It offers an integral view on the issue, it is capable in dealing with uncertainties and it opens the way to creative and anticipative solutions. Dealing with adaptation to climate change requires a shift in mindset; from a technical rational way of thinking towards an integral proactive one. A new era in spatial design and planning looms on the horizon. "Mounting evidence suggests climate change is going to be much worse much sooner than most people expect with little chance remaining of capping the rise in global temperatures at just two degrees and no better than a 50-50 chance of stabilising at a four degree increase. So a book like this is absolutely vital as a guide to what we can do and how we can cope". Ken Livingstone, former mayor of London "We must urgently phase out coal emissions and move to the post fossil fuel era, if we wish to preserve a tolerable planet for our children and grandchildren. Yet even so, society must prepare for some effects of climate change that have become inevitable. This book shows how." James E. Hansen, Director NASA Goddard Institute for Space Studies and Adjunct Professor Earth and Environmental Sciences, Columbia University, New York "Climate change is one of the biggest global problems mankind faces in the next centuries. People all over the world will need to save energy and use sustainable resources only. Meanwhile, they need to adapt to the effects of climate change urgently. In this book a very important contribution is made on the possibilities of spatial planning and design to enhance a high-qualitative adaptation, which can be applied over the entire globe." Prof. Dr. Victor Sergeev, MGIMO University - Center for the Studies of Global Problems, Moscow, Russia "The necessity to adapt to climate change offers us also a chance: this enhances us to improve the spatial quality of regions and to create valuable, liveable and worthwhile landscapes and urban environments. This book illuminates the way adaptation to climate change can be tackled in a spatial way. The many examples from Groningen province illustrate our frontrunner position in this field." Marc Calon, Regional Minister of Spatial Affairs, Finance, Area Development and Estate Development Corporation Policy, Province of Groningen.